Egg yolk phosphatidylcholine: Extraction, purification and its potential neuroprotective effect on PC12 cells. (May 2019) - Chen, Jin; Lin, Songyi; Sun, Na; Bao, Zhijie; Shen, Jiaying; Lu, Xueqi
Graphical abstract: Highlights: Egg yolk PC with high purity of 98% was obtained by silica column chromatography. Egg yolk PC showed a neuroprotective effect by inhibiting oxidative stress. The neuroprotective effect might be attributed to unsaturated fatty acids in PC. These unsaturated fatty acids were distributed in 9 kinds of PC molecular species. Abstract: Phosphatidylcholine (PC), a main phospholipid component in egg yolk, provides nourishment and protection for the body. In this study, an attempt has been made to explore the neuroprotective effect of PC that extracted and purified from egg yolk and its corresponding molecular species profile. Egg-yolk PC was obtained by solvent extraction and silica column chromatography, and the purity reached 98%. The neuroprotective effect of egg-yolk PC was investigated via scopolamine-induced PC12 cell model. The results indicated that the pre-treatment of egg-yolk PC could inhibit scopolamine-induced neurotoxicity and oxidative stress in PC12 cells via down-regulation of acetylcholinesterase (AChE) activity, monoamine oxidase (MAO) activity, and the malonaldehyde (MDA) level. This neuroprotective effect might be attributed to plentiful unsaturated fatty acids in egg-yolk PC that was identified to possess 9 kinds of molecular species including 16:0/16:0-PC, 16:0/16:1 Δ9 -PC, 16:0/18:0-PC, 16:0/18:1 Δ9 -PC, 16:0/18:2 Δ9, 12 -PC, 18:0/18:1 Δ9 -PC, 18:0/18:2 Δ9, 12 -PC, 18:1/18:2 Δ9, 12 -PC and 18:0/20:4 Δ5, 8, 11, 14 -PC by MALDI TOF-MS combined with GC-MS.